Mallard winter use of conservation program and nonprogram lands in Mississippi - Joseph D. Lancaster; Melanie R. Boudreau; Richard M. Kaminski; Garett M. Street; Anne E. Mini; Kevin D. Nelms; J. Brian Davis (Wildlife Society Bulletin)
Abstract Prior to the 19th century, the Mississippi Alluvial Valley (MAV) was a vast bottomland hardwood forest ecosystem with associated wetlands and intrinsic resources. Conversion for human uses in the 20th century transformed the MAV into an agriculturally dominated system. Since the late 1980s, federal and state incentivized conservation programs for landowners have helped restore wetlands on private lands in the MAV. Given the need to evaluate incentivized private lands in relation to waterfowl use, we used a sample of 241 radiomarked female mallards (Anas platyrhynchos) and evaluated their use of private and public lands in the Mississippi portion of the MAV during winters 2010–2015. Our objective was to examine mallard use of public, incentivized private, and non‐incentivized private lands and to evaluate if use changed by time of day and during and after the hunting season. Among all diurnal and nocturnal locations of mallards, 43.3% (n = 3,995) occurred on public lands, 19.5% (n = 1,802) were on incentivized private lands, and 37.2% (n = 3,432) on non‐incentivized private lands. Of mallard locations on incentivized private lands, mallards exhibited greatest use of Wetland Reserve Easements (WRE; 12.4%) and Conservation Reserve Program tracts (CRP; 4.7%). Mallards used public lands more diurnally within hunting seasons and more during hunting seasons than post‐hunting season, which we attributed to the presence of designated sanctuaries that may have provided refuge from hunting and other disturbances. Post‐hunting season, mallards increased their use of incentivized and non‐incentivized private lands, perhaps to exploit seasonal emergent wetland and remnant agricultural foods. Radiomarked mallards used a variety of landcover types across public and private land, reinforcing the importance of habitat complexes for wintering mallards and other dabbling ducks. Conservation program lands, such as CRP and WREs, provide emergent and forested wetlands that complement flooded agricultural lands and natural wetlands in the MAV. When areal availability estimates of incentivized private lands are accessible from government or other partners, we encourage future researchers to investigate selectivity by mallards and other waterfowl of public, incentivized, and non‐incentivized lands.